Measuring Dependency of International Trade Aerospace Sector - Intan Perwitasari; Daffa Rizqi Prayudya (Economics Development Analysis Journal, 2022)
This research aims to quantify the specialization stage of Indonesia, followed by the dependencies of Indonesia's imports on the aerospace sector. Since, there are still few studies about the aerospace sector, especially from an economic perspective. This research conducted to fulfill the gap studies on international trade aerospace sector phenomenon. The sample used in this research is 9 countries between 2001 – 2018. Methods will be conducted in two steps. First, by using Trade Specialization Index (TSI), we try to identify the specialization stage of each country in the aerospace sector. Second, we used Import Dependency Ratio (IDR) to identify the level of Indonesia's dependency in the aerospace sector on other countries. We found that Indonesia still reaching the introduction stage of specialization. Adding relevancy to the result, Indonesia is also considered as highly-dependent on other countries in terms of the aerospace sector. We therefore suggest that Indonesia needs to raise traction in the aerospace sector by increasing its budget and conducting technology transfers, so Indonesia’s competitiveness will raised.